1988
DOI: 10.2337/diacare.11.10.850
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Captopril and Nifedipine in Normotensive Patients With Incipient Diabetic Nephropathy

Abstract: In these studies, the effect of a 6-wk treatment by placebo, the calcium-channel blocker nifedipine, or the converting-enzyme inhibitor captopril was assessed in normotensive patients with insulin-dependent diabetes and incipient nephropathy. In response to captopril and nifedipine, arterial pressure decreased slightly and to a similar extent. These drugs resulted in opposite effects on urinary excretion of albumin [i.e., increase in urinary albumin excretion (UAE) by 40% during nifedipine treatment and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The importance of this early effect is bolstered further by the findings in the RENAAL, IDNT, and AASK trials. Thus, it is clear that the projection made more than a decade ago that reductions in proteinuria correlated with a slowed progression of kidney disease now are supported by several clinical trials (48,49).…”
Section: Resultsmentioning
confidence: 97%
“…The importance of this early effect is bolstered further by the findings in the RENAAL, IDNT, and AASK trials. Thus, it is clear that the projection made more than a decade ago that reductions in proteinuria correlated with a slowed progression of kidney disease now are supported by several clinical trials (48,49).…”
Section: Resultsmentioning
confidence: 97%
“…This disparate effect on proteinuria of CEI and calcium antagonist has been previously reported in rats 27 -28 and patients. 39 As discussed above, the renal hemodynamic profiles of these two classes of antihypertensive agents are distinctly different. In particular, although it is clear that CEIs reduce glomerular capillary pressure in addition to systemic blood pressures, 1314 equivalent reduction in systemic pressure with a CCB may not lower glomerular capillary pressure 2021 because of a concomitant reduction in preglomerular resist-ances 19 and impairment of renal autoregulatory responses.…”
mentioning
confidence: 99%
“…tive) on proteinuria in streptozotocin diabetic rats. Mimran et al 36 reported an increase in urinary albumin excretion with nifedipine (a dihydropyridine derivative) treatment in insulin-dependent diabetic patients with incipient diabetic nephropathy (urinary albumin excretion >15 jig/min). This is in contrast to the results reported by the Melbourne Diabetic Nephropathy Study Group, 37 in which nifedipine treatment significantly reduced albuminuria in hypertensive diabetic patients.…”
Section: Discussionmentioning
confidence: 99%